Mineralization and humification of chicken manure and composted kitchen waste in soils based on an in situ litter-bag experiment: impacts of organic inputs and microbial community - Yujia SHI; Haixia ZENG; Linfa FANG; Yue DENG; Ran XIAO (Frontiers of Agricultural Science and Engineering)
Organic inputs are key to increasing soil organic carbon in agricultural soils. This study aimed to unravel the process of mineralization and humification of chicken manure (CM) and composted kitchen waste (KW) using an in situ litter-bag incubation experiment. The results indicated that over 50%, 64% to 72%, and 62% to 85% of the initial mass, carbon and nitrogen, respectively, were lost through incubation with a marked loss occurring during the first 28 days. Increased humic acids (HAs), humus (HS) and degree of humification, along with a decrease in the level of fulvic acids and precursors for humic substances were observed through incubation. By comparison, CM demonstrated higher carbon and nitrogen conservation efficiencies and greater humification compared to KW. Additionally, a higher degree of humifaction and larger quantities of HAs and HS were not favorable for carbon and nitrogen conservation. Further structural equation modeling indicated that microbial community had a strong effect on carbon loss and nitrogen release, while stoichiometric properties of organic inputs were the main determinant of the mineralization and humification processes. These findings will enhance understanding of litter decomposition in soils and provide valuable references for soil carbon sequestration with organic inputs.